Consuming Alone: Broadening Putnam's "Bowling Alone" Thesis. Issue 9 (September 2015) - Rauch, Andreas; Deker, Johannes S.; Woodside, Arch G.
ABSTRACT Despite the popularity of Wi‐Fi technologies and social networks, many residents in developed nations are more socially isolated now than a few decades ago. Applying fuzzy‐set qualitative comparative analysis, using a nationally representative sample in one developed nation this study investigates the relationship between social isolation and advice‐giving and advice‐seeking behaviors with regard to brands or products. This study raises the proposition that people who are socially isolated lack the opportunity to give and seek advice, and, thus, abstain from doing so. Additionally, the study proposes that lacking ability or motivation also represent causal conditions for isolation. The study also investigates consumer behavior outcomes of low advice‐giving and advice‐seeking behaviors; that is, pampering and status buying. The findings from an analysis of an omnibus annual survey of residents in one nation support the propositions that the study proposes from theory and are likely relevant for residents of most developed nations.